Effect of diabetes mellitus on coronary plaque characteristics and progression by serial Coronary Computed Tomography Angiography (CCTA). (14th October 2021) - Lakshmanan, S; Kinninger, A; Nakanishi, R; Shekar, C; Shaikh, K; Dahal, S; Nezarat, N; Roy, S K; Budoff, M J
Abstract: Background: Diabetes Mellitus (DM) is a major risk factor for coronary artery disease (CAD) and associated poor outcomes. There is a higher incidence of major adverse cardiac events in patients with DM than those without DM. Coronary plaque characteristics measured by CCTA are correlated with adverse cardiovascular (CV) outcomes. Purpose: We sought to evaluate coronary plaque characteristics as well as rates of progression of coronary plaque burden as measured by serial CCTA in patients with DM and those without DM. Methods: The study population included a total of 403 participants (mean age 61.4±11.4 years, 53% men; median scan interval 1.5 years) who were prospectively enrolled in serial CCTA trials. We identified 212 participants with DM and 191 participants without DM, who had undergone serial CCTA. Coronary Plaque volumes were measured and characterized as low attenuation plaque (LAP), total non-calcified plaque (TNCP) and total plaque (TP) using semi-automated plaque analysis software (Qangio medis). Multivariate linear regression was used to examine the effect of DM on coronary plaque progression. Results: Patients with DM had greater rates of progression of normalized TP volume (median change in annualized plaque (IQR): 39.1 (9.9–114.4) in DM vs 23.5 (4.1–63.8) mm 3 in non-DM, p=0.001), TNCP volume (21.6 (3.3–60.8) in DM vs 8.7 (0.1–35.6) mm 3 in non-DM, p=0.003) and LAP volumes (0.7 (−0.6 to 7.8) in DM vs 0.1 (−0.4 to 1.9) mm 3 in non-DM, p=0.04). After adjusting for relevant risk factors and baseline plaque, the annualized rates of progression were higher in patients with DM by 28% for TP (p=0.004), 27% for TNCP (p=0.011), 23% for fibrous plaque (p=0.026) and by 42% LAP (p=0.050), compared to those without DM. Conclusion: Patients with DM have significantly higher rates of coronary plaque progression, including vulnerable LAP, than those without DM. Our findings reveal differences in rates, burden and characteristics of coronary plaque progression in patients with DM vs those without DM. These results provide mechanistic understanding of natural history of coronary atherosclerosis in this vulnerable population, that could explain the increased risk of CV events among patients with DM. Coronary atherosclerotic phenotyping by CCTA could serve as a potential surrogate measure for risk stratification and evaluation in clinical trials to examine therapeutic strategies in this vulnerable population. Funding Acknowledgement: Type of funding sources: None.